Bioactivities of Achillea phrygia and Bupleurum croceum based on the composition of phenolic compounds: In vitro and in silico approaches - EMRE, GİZEM; DOĞAN, AHMET (My University, 2017)
This study presents the effects of the Achillea phrygia Boiss. et Bal. and Bupleurum croceum Fenzl. extracts obtained by different solvents (ethyl acetate, methanol and water) on selected enzyme inhibitory effects and antioxidant ability with screening bioactive compounds. Total and individual bioactive compounds were detected by spectrophotometric and HPLC-DAD techniques. Antioxidant abilities were evaluated by different methods including free radical scavenging (ABTS and DPPH), reducing power (CUPRAC and FRAP), phosphomolybdenum and metal chelating. Enzyme inhibitory effects were tested against cholinesterases, tyrosinase, amylase, glucosidase and lipase. Total phenolic contents were ranged from 20.52 mgGAE/g extract (B. croceum methanol extract) to 41.13 mgGAE/g extract (A. phrygia methanol extract). Generally, methanol and water extracts showed the strongest antioxidant abilities, while the ethyl acetate extracts had the most promising enzyme inhibitory effects. HPLC analysis revealed the abundance of some phenolics including rutin, quercetin, sinapic acid and chlorogenic acid, respectively. These components were also assessed using molecular modelling with the aim to study their docking properties on a set of six enzymes used in this study. Overall, these species could be suggested as valuable sources of natural-bioactive agents for developing new functional, pharmacological and health promoting ingredients. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Agricultural Sciences; Agriculture; Food Engineering; Life Sciences; Health Sciences; Natural Sciences; Engineering and Technology; GIDA BİLİMİ VE TEKNOLOJİSİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); TOKSİKOLOJİ; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); FOOD SCIENCE & TECHNOLOGY; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); TOXICOLOGY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Toksikoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Sağlık, Toksikoloji ve Mutajenez; Yemek bilimi; Fizik Bilimleri; Toxicology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Health, Toxicology and Mutagenesis; Food Science; Physical Sciences; Achiella phrygia; Bupleurum croceum; Bioactive compounds; Natural agents; Turkey; ANTIOXIDANT ACTIVITY; MILLEFOLIUM L.; BIOLOGICAL-ACTIVITIES; CHLOROGENIC ACIDS; CRYSTAL-STRUCTURE; POTENTIAL SOURCES; ASPHODELINE TAXA; NATURAL AGENTS; ALPHA-AMYLASE; ESSENTIAL OIL; Achiella phrygia; Bupleurum croceum; Bioactive compounds; Natural agents; Turkey